Nonadherence to Medication Therapy in Haemodialysis Patients: A Systematic Review. - Saurav Ghimire; Ronald L Castelino; Nicole M Lioufas; Gregory M Peterson; Syed Tabish R Zaidi (PLoS ONE)
Background End-stage kidney disease (ESKD) patients are often prescribed multiple medications. Together with a demanding weekly schedule of dialysis sessions, increased number of medicines and associated regimen complexity pre-dispose them at high risk of medication nonadherence. This review summarizes existing literature on nonadherence and identifies factors associated with nonadherence to medication therapy in patients undergoing haemodialysis. Methods A comprehensive search of PubMed, Embase, CINAHL, PsycInfo, and Cochrane Database of Systematic Reviews covering the period from 1970 through November 2014 was performed following a predefined inclusion and exclusion criteria. Reference lists from relevant materials were reviewed. Data on study characteristics, measures of nonadherence, prevalence rates and factors associated with nonadherence were collected. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines was followed in conducting this systematic review. Results Of 920 relevant publications, 44 were included. The prevalence of medication nonadherence varied from 12.5% to 98.6%, with widespread heterogeneity in measures and definitions employed. Most common patient-related factors significantly associated with nonadherence were younger age, non-Caucasian ethnicity, illness interfering family life, being a smoker, and living single and being divorced or widowed. Similarly, disease-related factors include longevity of haemodialysis, recurrent hospitalization, depressive symptoms and having concomitant illness like diabetes and hypertension. Medication-related factors such as daily tablet count, total pill burden, number of phosphate binders prescribed and complexity of medication regimen were also associated with poor adherence. Conclusions A number of patient-, disease-, and medication-related factors are associated with medication nonadherence in haemodialysis patients. Clinicians should be aware of such factors so that adherence to medications can be optimised in haemodialysis patients. Future research should be directed towards well-designed prospective longitudinal studies developing standard definitions and validating available measurement tools, while focusing on the role of additional factors such as psychosocial and behavioural factors in predicting nonadherence to medications.